Urine miRNA signature as potential non-invasive diagnostic biomarker for Hirschsprung’s disease - Sreepada, Abhijit; Khasanov, Rasul; Elkrewi, Enas; Torre, Carolina de la; Felcht, Judith; Abdulqader, Ahmad Abdulrahman A. al-; Martel, Richard; Hoyos Celis, Nicolas Andres; Boettcher, Michael; Wessel, Lucas; Schäfer, Karl Herbert; Tapia-Laliena, María Angeles (Frontiers in molecular neuroscience, 2025)
Hirschsprung’s disease (HSCR) is characterized by congenital absence of ganglion cells in the gastrointestinal tract, which leads to impaired defecation, constipation and intestinal obstruction. The current diagnosis of HSCR is based on Rectal Suction Biopsies (RSBs), which could be complex in newborns. Occasionally, there is a delay in diagnosis that can increase the risk of clinical complications. Consequently, there is room for new non-invasive diagnostic methods that are objective, more logistically feasible and also deliver a far earlier base for a potential surgical intervention. In recent years, microRNA (miRNA) has come into the focus as a relevant early marker that could provide more insights into the etiology and progression of diseases. Therefore, in the search of a non-invasive HSCR biomarker, we analyzed miRNA expression in urine samples of HSCR patients. Results from 5 HSCR patients using microarrays, revealed hsa-miR-378 h, hsa-miR-210-5p, hsa-miR-6876-3p, hsa-miR-634 and hsa-miR-6883-3p as the most upregulated miRNAs; while hsa-miR-4443, hsa-miR-22-3p, hsa-miR-4732-5p, hsa-miR-3187-5p, and hsa-miR-371b-5p where the most downregulated miRNAs. Further search in miRNAwalk and miRDB databases showed that certainly most of these dysregulated miRNAs identified target HSCR associated genes, such as RET, GDNF, BDNF, EDN3, EDNRB, ERBB, NRG1, SOX10; and other genes implied in neuronal migration and neurogenesis. Finally, we could also validate some of these miRNA changes in HSCR urine by RT-qPCR. Altogether, our analyzed HSCR cohort presents a dysregulated miRNA expression presents that can be detected in urine. Our findings open the possibility of using specific urine miRNA signatures as non-invasive HSCR diagnosis method in the future.